2023
DOI: 10.1108/ijrdm-05-2022-0153
|View full text |Cite
|
Sign up to set email alerts
|

Adopting retail technology in crises: integrating TAM and prospect theory perspectives

Abstract: PurposeThis paper combines prospect theory (PT) and the technology acceptance model (TAM) proposing that technology anxiety (TA), risk averseness (RA), concern and resistance to use inhibit technology acceptance, while trust, social influence (SI) and compatibility are enablers to technology acceptance, particularly in the context of consumer adoption of retail technologies during crises.Design/methodology/approachA review of PT and TAM literature was conducted to develop a model which considers the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In addition, it is important to consider the impact of external factors such as government policies, economic conditions, and technological advancements on the B2C sector. Studies on purchasing behavior have explored the adoption and usage of new technologies, particularly delivery services, that were necessitated by the pandemic [15,16,53,[83][84][85], as well as identifying factors that have influenced changing consumer behavior [62,68,70,73,86,87]. In contrast, the pandemic has brought sustainability-related issues to the forefront, including food waste and security from a consumer perspective.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In addition, it is important to consider the impact of external factors such as government policies, economic conditions, and technological advancements on the B2C sector. Studies on purchasing behavior have explored the adoption and usage of new technologies, particularly delivery services, that were necessitated by the pandemic [15,16,53,[83][84][85], as well as identifying factors that have influenced changing consumer behavior [62,68,70,73,86,87]. In contrast, the pandemic has brought sustainability-related issues to the forefront, including food waste and security from a consumer perspective.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Given this background, while the positive influence of PU, PEU and PE on attitudes toward technology adoption and/or intention to adopt online shopping is well documented (e.g. Bhatt, 2022;Burgess et al, 2023;Driediger and Bhatiasevi, 2019;Nguyen et al, 2023;Thomas-Francois and Somogyi, 2022), the direct influence of these three antecedents (PEU, PU and PE) of TAM on actual adoption of web-based retail shopping is little known. To address this gap, the following hypotheses are formulated:…”
Section: Pu Peu Pe and Web-based Retail Shopping Behaviourmentioning
confidence: 99%
“…The Technology Acceptance Model (TAM) was proposed by Fred Davis (1985) (Burgess et al, 2023)TAM is a basic model that aims to predict the adoption of any technological advancement and is a leading theory used to study technology adoption quantitatively. According to TAM, the intention to accept or use a new technology is determined by perceived ease of use and perceived use (Cahyono et al, 2024).…”
Section: Theory Of Reasoned Action (Tam)mentioning
confidence: 99%
“…Research Cahyono et al, (2024) and Burgess et al, (2023) It has been shown that TAM can be used to study user behavior in e-commerce, user convenience perceptions and usage attitudes. Research Keni et al, (2024) and Tobias-Mamina et al, (2023) has shown that TRA can be used to study user behavior in a variety of contexts, such as social media use and purchase intention and marketing strategies.…”
Section: Introductionmentioning
confidence: 99%